2019
DOI: 10.1002/slct.201901722
|View full text |Cite
|
Sign up to set email alerts
|

Development of Practical Electrochemical System for Phenytoin Detection

Abstract: In this work a practical electrochemical approach has been developed by using gold (Au)-film electrode for phenytoin detection. The formation of Au-film was monitored by using scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy techniques. After the electrochemical characterization, the experimental conditions were optimized and then the analytical characterizations were examined. As a result, two linear ranges were found between 5x10 À 7 M and 2x10 À 4 M wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Considering this relationship, it is known that gradient values equal to 0.5 demonstrates a diffusion‐controlled mechanism while gradient values of 1.0 belongs to an adsorption‐controlled electrochemical mechanism. From this point of view, it was concluded that for dopamine detection at PDI‐ C 8 SAc/CFE mostly diffusion controlled mechanism has taken place …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this relationship, it is known that gradient values equal to 0.5 demonstrates a diffusion‐controlled mechanism while gradient values of 1.0 belongs to an adsorption‐controlled electrochemical mechanism. From this point of view, it was concluded that for dopamine detection at PDI‐ C 8 SAc/CFE mostly diffusion controlled mechanism has taken place …”
Section: Resultsmentioning
confidence: 99%
“…From this point of view, it was concluded that for dopamine detection at PDI-C 8 SAc/CFE mostly diffusion controlled mechanism has taken place. [12][13][14]…”
Section: Examination Of Scan Rate Effectmentioning
confidence: 99%